Health Risk From Nitrate Exposure in Gravity Feed System, GFS Water Among Residents of 20th Mile Village, Hulu Langat, Selangor - Md Yusoff, Muhammad Syafiq; Mohd Sham, Shaharuddin; Adriyani, Retno (JPKM: Jurnal Profesi Kesehatan Masyarakat, 2025)
Nitrate in drinking water, particularly from non-conventional sources like the Gravity Feed System, GFS in Hulu Langat, poses a potential health risk to the population. Therefore, a study is necessary to ensure compliance with the National Standards for Drinking Water Quality and to assess the extent of the resulting non-carcinogenic hazard. A cross-sectional study was conducted to estimate the risk of exposure to nitrate via the Gravity Feed System, GFS water ingestion pathway for the Hulu Langat population. The objective was to examine the health risk associated with exposure to nitrate in the Gravity Feed System, GFS among the population in Hulu Langat, Selangor. A total of 88 respondents with 35 sample water who fulfilled the inclusive criteria were selected in housing areas of Hulu Langat. Questionnaires were administered to determine the information of respondents. Duplicate samples were collected from the kitchen tap using HDPE bottles to determine the nitrate concentration using a HI801-02 Iris Visible Spectrophotometer and the pH using a HI-98129 pH Meter, both from Hanna Instruments. The mean and standard deviation nitrate concentration was 2.4917±1.2610, pH concentration was 7.0680±0.2843 and Hazard Quotient (HQ) was 0.0084±0.0060. All samples did not exceed the National Standard for Drinking Water Quality (NSDWQ), with the maximum result for this study being 5.30 mg/L and was not a significant health concern since all Hazard Quotient (HQ) values were below 1. There was no statistically significant correlation between pH level and nitrate using Pearson correlation test. To conclude, non-carcinogenic risk attributable to nitrate ingestion in Hulu Langat Gravity Feed System, GFS water was negligible.